Diagnóstico de segurança alimentar e sua correlação com doenças crônicas em um município do Sudoeste do Paraná - Silva, Emanuele Kelli Samaia (2024)
Food and nutritional insecurity is a multifactorial problem that affects a large part of the world's population. Individuals who have difficulties in accessing and acquiring food in sufficient quantity and quality to guarantee the right to adequate and healthy food in a dignified manner are classified as insecure. The Brazilian Food Insecurity Scale (EBIA) is an important instrument for verifying the degree of insecurity in which the family is inserted, and can present the classification of food security, mild, moderate or severe food insecurity, taking into account concerns of a shortage food even more worrying cases such as lack of food for long periods. Considering the profound dimension of this problem, the quality of life and health conditions of individuals are also affected and may intensify pre-existing chronic diseases. Therefore, the objective of this research is to carry out a diagnosis of food and nutritional security in the municipality of Francisco Beltrão/PR. This is a quantitative research composed of men/women living in the city of Francisco Beltrão/PR, the project was submitted and approved by the Ethics Committee for Research with Human Beings of the State University of Western Paraná (UNIOESTE) CAE nº 62685922.0. 0000.0107. It was possible to notice a higher prevalence of female individuals (82.9%), as well as a higher classification of food security (72.1%), followed by mild food insecurity (22.5%). Furthermore, there was a high incidence of diseases such as diabetes mellitus, systemic arterial hypertension and depression in the individuals interviewed. In relation to the other sociodemographic variables, a lower level of education was noted, with elementary school being the most mentioned (41.4%). Considering self-perception of quality of life, all domains were classified as ‘’regular’’. There was also a significant correlation between the degree of food security and health conditions, in which there is a greater presence of pathologies, which demonstrates a concern regarding the nutritional care of these individuals, considering that the highest prevalence is of diseases that require adequate dietary restriction to control them. Therefore, it is extremely important to stratify and contain the risk of food and nutritional insecurity.